Bridging the soft skills gap : how to teach the missing basics to today's young talent - Tulgan, Bruce (Hoboken, NJ : Jossey-Bass, a Wiley imprint, 2015)
Based on more than twenty years of research, renowned expert on the Millennial workforce Bruce Tulgan offers concrete solutions to help managers teach the missing basics of professionalism, critical thinking, and followership$1 (Bcomplete with 92 step-by-step lesson plans designed to be highly flexible and easy to use. --s
Includes index.
Description based on print version record and CIP data provided by publisher.
Keywords: Soft skills; Generation Y -- Employment; Business etiquette; Personnel management; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Electronic books